The gut microbiota composition is linked to subsequent occurrence of ventilator-associated pneumonia in critically ill patients - Arthur Orieux; Raphaël Enaud; Sébastien Imbert; Philippe Boyer; Erwan Begot; Adrian Camino; Alexandre Boyer; Patrick Berger; Didier Gruson; Laurence Delhaes; Renaud Prevel (Microbiology Spectrum, 2023)
ABSTRACT Ventilator-associated pneumonia (VAP) is the most frequent nosocomial infection in critically ill-ventilated patients. Oropharyngeal and lung microbiota have been demonstrated to be associated with VAP occurrence, but the involvement of gut microbiota has not been investigated so far. Therefore, the aim of this study is to compare the composition of the gut microbiota between patients who subsequently develop VAP and those who do not. A rectal swab was performed at admission of every consecutive patient into the intensive care unit (ICU) from October 2019 to March 2020. After DNA extraction, V3-V4 and internal transcribed spacer 2 regions deep-sequencing was performed on MiSeq sequencer (Illumina) and data were analyzed using Divisive Amplicon Denoising Algorithm 2 (DADA2) pipeline. Among 255 patients screened, 42 (16%) patients with invasive mechanical ventilation for more than 48 h were included, 18 (43%) with definite VAP and 24 without (57%). Patients who later developed VAP had similar gut bacteriobiota and mycobiota α-diversities compared to those who did not develop VAP. However, gut mycobiota was dissimilar (β-diversity) between these two groups. The presence of Megasphaera massiliensis was associated with the absence of VAP occurrence, whereas the presence of the fungal genus Alternaria sp. was associated with the occurrence of VAP. The composition of the gut microbiota, but not α-diversity, differs between critically ill patients who subsequently develop VAP and those who do not. This study encourages large multicenter cohort studies investigating the role of gut-lung axis and oropharyngeal colonization in the development of VAP in ICU patients. Trial registration number: NCT04131569, date of registration: 18 October 2019. IMPORTANCE The composition of the gut microbiota, but not α-diversity, differs between critically ill patients who subsequently develop ventilator-associated pneumonia (VAP) and those who do not. Investigating gut microbiota composition could help to tailor probiotics to provide protection against VAP.